Whipple-ables: clinicopathologic comparison of 1032 cancers removed by pancreatoduodenectomy based on pathologic re-review using refined site-specific criteria - Balcı, Serdar; Reid, Michelle; Erbarut Seven, İpek; Saka, Burcu; Pehlivanoğlu, Burçin; Memiş, Bahar; Bağcı, Pelin; Baştürk, Olca; Adsay, N. Volkan (Nature Publishing Group, 2020)
Background: The literature is highly conflicted on the differential clinicopathologic characteristics of cancers arising from differentcompartments of the ampulla-pancreato-biliary tract and duodenum that are removed by pancreatoduodenectomy (Whipple) operation,largely due to differences in the criteria employed (or lack thereof) in the site-specific classification of these cancers until recently. Lack ofstandardized grossing approaches and careful evaluation appear to be significant contributors to the controversy.
Keywords: Clinicopathologic Comparison; Cancers; Pancreatoduodenectomy